Синтез наноколлоидов на основе оксида алюминия; Известия вузов. Физика; Т. 58, № 2-2 - Скуридин В. С. Виктор Сергеевич; Садкин В. Л. Владимир Леонидович; Стасюк Е. С. Елена Сергеевна; Варламова Н. В. Наталья Валерьевна; Рогов А. С. Александр Сергеевич; Нестеров Е. А. Евгений Александрович; Ильина Е. А. Екатерина Алексеевна; Слепченко Г. Б. Галина Борисовна (2015, 2015)
Заглавие с экрана